Ramadan exposure in utero and child mortality in Burkina Faso: analysis of a population-based cohort including 41,025 children - Schoeps, Anja; Ewijk, Reyn van; Kynast-Wolf, Gisela; Nebié, Eric; Zabré, Pascal; Sié, Ali; Gabrysch, Sabine (American journal of epidemiology, 2018)
Abstract. Ramadan exposure in utero can be regarded as a natural experiment with which to study how nutritional conditions in utero influence susceptibility to
Gesehen am 22.04.2020